The Relationship Of Temporary Job Rotation And Nurse Work Stress - Rusdi, Rusdi; Mohd Said, Faridah; Umar, Nur Syazana (Sahabat Publikasi Kuu, 2024)
Background: Work rotation does not always have a positive impact; productivity will decrease due to moving nurses to a new position, so there needs to be an adjustment again. In this type of temporary work rotation, there is a risk of problems because it is carried out in a relatively short period, and there is a lack of opportunity to adapt to a new environment, which can increase the work stress of nurses. Objective: To analyze the relationship between temporary work rotation and work stress of nurses in the Inpatient Hospital of the Hospital. Methods: Descriptive analytical research design with a cross-sectional approach, a total sample of 54 respondents selected using the Proportional Random Sampling technique. Results: The analysis test showed that as many as (53.7%) of respondents rated the temporary work rotation activity as